2018
DOI: 10.1038/s41598-018-31730-w
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression Impairs the Use of Reward Values for Decision-Making

Abstract: Depression is a debilitating condition with a high prevalence. Depressed patients have been shown to be diminished in their ability to integrate their reinforcement history to adjust future behaviour during instrumental reward learning tasks. Here, we tested whether such impairments could also be observed in a Pavlovian conditioning task. We recruited and analysed 32 subjects, 15 with depression and 17 healthy controls, to study behavioural group differences in learning and decision-making. Participants had to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 27 publications
(43 reference statements)
8
38
0
Order By: Relevance
“…Moreover, in Pavlovian conditioning paradigms, depressed participants tend to demonstrate less accurate reward contingency predictions during or after the conditioning phase (Kumar et al, 2008;Robinson et al, 2012, although see Lawson et al, 2017and Rupprechter, Stankevicius, Huys, Steele, & Seriès, 2018 for no group differences). By contrast, behavioural punishment conditioning does not seem to differ between depressed and control subjects when assessed with explicit measures (although neural group effects have been observed, see below; Lawson et al, 2017;Robinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Pavlovian conditioning paradigms, depressed participants tend to demonstrate less accurate reward contingency predictions during or after the conditioning phase (Kumar et al, 2008;Robinson et al, 2012, although see Lawson et al, 2017and Rupprechter, Stankevicius, Huys, Steele, & Seriès, 2018 for no group differences). By contrast, behavioural punishment conditioning does not seem to differ between depressed and control subjects when assessed with explicit measures (although neural group effects have been observed, see below; Lawson et al, 2017;Robinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the lack of doing things one enjoys, or leaving the house daily to improve mood in this sub-group may be a by-product of this learned-helplessness wherein individuals may believe such strategies to be futile in reducing their chances of suffering form depression. 23 However, it is not clear why such difference existed for only these two self-help behaviors and only in men, not in women. On the other hand, men who underestimated their risk of developing a MDE were also less likely to "do something they enjoy".…”
Section: Discussionmentioning
confidence: 98%
“…The SSUS has good internal consistency in this study (Cronbach's a = 0.78), which is consistent with the alpha value of development (Cronbach's a = 0.80). 23 Self-help behaviours were scored on a scale of 0-4 per behaviour, with higher scores indicating increased frequency of participation of said self-help behaviours. Total self-help scores were determined by adding up the score of each individual self-help behaviour.…”
Section: Measurementsmentioning
confidence: 99%
“…This hyposensitivity to reward might also affect reward-based decision-making in individuals with depression. Evidence suggests that depression is associated with a reduced ability to maximize rewards by decision-making (e.g., [2,3]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as for the memory rate, Dombrovski et al [11] found that, regarding patients with depression and a history of attempted suicide, the only difference from healthy individuals was a lower memory rate after stimulus reversal. In addition, Rupprechter et al [3] found that in simple reward-value estimations, unmedicated depression patients exhibit lower memory rates than learning rates. However, Chase et al [12] reported no change in the learning rate after stimulus reversal in reversal-learning tasks.…”
Section: Introductionmentioning
confidence: 99%